2018
DOI: 10.1021/acsinfecdis.7b00231
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Proteostasis Network for Mycobacterial Drug Discovery

Abstract: Tuberculosis (TB), caused by Mycobacterium tuberculosis (Mtb), remains one of the world’s deadliest infectious diseases and urgently requires new antibiotics to treat drug-resistant strains and to decrease the duration of therapy. During infection, Mtb encounters numerous stresses associated with host immunity, including hypoxia, reactive oxygen and nitrogen species, mild acidity, nutrient starvation, and metal sequestration and intoxication. The Mtb proteostasis network, composed of chaperones, proteases, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 238 publications
(551 reference statements)
1
62
0
1
Order By: Relevance
“…Proper protein homeostasis is a vital aspect of bacterial growth and, in some cases, of bacterial virulence (Lupoli et al, 2018;Culp & Wright, 2017). Of the bacterial proteasome complexes, Clp is the most validated therapeutic target (Raju et al, 2012;Lee & Suh, 2016;Zhou et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proper protein homeostasis is a vital aspect of bacterial growth and, in some cases, of bacterial virulence (Lupoli et al, 2018;Culp & Wright, 2017). Of the bacterial proteasome complexes, Clp is the most validated therapeutic target (Raju et al, 2012;Lee & Suh, 2016;Zhou et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several macrocyclic peptides that specifically interact with ClpC1 have been identified to disrupt the normal functioning of the proteasome (Lupoli et al, 2018). Cyclomarin A (CYMA) is structurally similar to the heptapeptide rufomycin I (RUF-I), while ohmyungsamycin A (OMS-A) and ohmyungsamycin B (OMS-B) are structurally similar to ecumicin (ECU) (Um et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…HtpG and DnaK are essential for cell growth, native protein folding and immune response. Several studies suggested DnaK and HtpG as potential drug target [26] [27].…”
Section: Resultsmentioning
confidence: 99%
“…In Mtb, proteostasis network provides protection from different stresses and host immunity. The machinery used for this comprises a complex network of chaperones, proteases, and a eukaryotic-like proteasome (functionally linked AAA -ATPases domain protein family) which helps in evading the host immunity by maintaining the integrity of the mycobacterial proteome 44 . Besides this, AAA -ATPases domain protein family also play a significant role in recognition of ESAT-6 secretion system (ESX-1) secreted virulence factors 45 , which is a type VII secretion system of Mtb and is capable to form pores and rupture phagosomes 46 .…”
Section: Discussionmentioning
confidence: 99%